Communication – the foundation for collaborative relationships amongst providers, and between providers and patients: A case in breast and colorectal cancer. (March 2014) - Lazure, Patrice; St-Germain, France; Gryfe, Robert; Trudeau, Maureen; Hayes, Sean M.
Abstract : Objectives: A national needs assessment was undertaken to determine the challenges, and their underlying causes experienced by Canadian healthcare providers caring for persons with breast or colorectal cancer, in their inter-professional and patient–provider clinical relationships. Methods and sample: A mixed-methods approach using an exploratory qualitative phase (semi-structured interviews), and a confirmatory quantitative phase (online survey) was employed. Sample included 223 providers. Results: Six challenges associated with patient–provider communication, were identified: providing emotional support, using language that a patient can understand, adjusting to the patient's informational needs, facilitating patients' participation in screening programs, empowering patients to participate actively in treatment decisions, and balancing treatment with impact on quality of life. Four additional challenges were reflective of inter-professional care issues: communication between oncology team and referring physicians, collective, and systematic medication reconciliation process, facilitation of patients' navigation through the continuum of care, and referral of patients in psychosocial distress. Discussion: This study highlighted the importance of assessing communication and collaboration skills and clinical behaviours of healthcare providers in order to provide complete and relevant educational recommendations. These findings could guide the design of educational programs and stimulate reflection amongst healthcare providers on the delivery of care to patients with breast or colorectal cancer.